Association of hair steroid hormone levels with habitual sleep quality in middle-aged and older women. (September 2021) - Mazgelytė, E.; Vysocka, A.; Narkevičius, M.; Burokienė, N.; Petrėnas, T.; Kaminskas, A.; Songailienė, J.; Utkus, A.; Karčiauskaitė, D.
Abstract : Background: Poor sleep quality is associated with negative effects on physical and mental health. It is suggested that dysregulation of hypothalamic-pituitary-adrenal (HPA) axis is an important mechanism through which sleep disturbances are related to adverse health outcomes. Previous studies explored the relationship between sleep quality and diurnal cortisol rhythms. Thus, we aimed to investigate the association between self-reported sleep quality and the long-term HPA axis activity by measuring hair cortisol, cortisone and DHEA levels. Methods: 143 women participating in Lithuanian cardiovascular risk prevention program were included in the study. Sleep quality was assessed using Pittsburgh Sleep Quality Index (PSQI). Hair steroid hormone levels were determined by LC-MS/MS. Results: Data showed that 83 (58.04%) women have poor habitual sleep quality (PSQI>5). The Mann-Whitney U-test revealed statistically significant difference in hair cortisol concentration between poor and good sleepers (median (IQR): 4.32 (11.25) ng/g vs. 3.04 (4.96) ng/g, p = 0.039). No significant differences in hair cortisone, DHEA levels and cortisol/DHEA ratio were observed between groups. Conclusion: Subjectively evaluated poor sleep quality is related to increased long-term cortisol secretion.